Relationship between CPITN and oral health behaviour in Japanese adults - Kawamura, M.; Sasahara, H.; Kawabata, K.; Iwamoto, Y.; Konishi, K.; Wright, F.A.C. (Australian dental journal, 1993)
Many studies on toothbrushing have concentrated on clinically diagnosing plaque and measuring periodontal status as indicators of oral health behaviour. From a behavioural point of view, however, the more important objective is the health behaviour itself. To investigate the relationship of oral health behaviour to periodontal status, 517 urban employees in Japan (249 men and 268 women aged 20–59 years) responded to a 20‐item dental health behaviour questionnaire, entitled the HU‐DBI, and had their periodontal conditions examined using the CPITN. Only 1 per cent were found with a healthy periodontium (Code 0), and 9 per cent had bleeding on probing (Code 1). Calculus (Code 2) was the most prevalent condition with 51 per cent of subjects having this code as the worst condition, followed by shallow pockets (Code 3) in 30 per cent, and deep pockets (Code 4) in 9 per cent of the sample. The mean HU‐DBI score was 4.2 (out of 12). Females had somewhat higher scores than males (4.4 vs. 4.0, p<0.05). CPITN had a negative relationship with the HU‐DBI (r=‐0.26, p<0.001), and a positive relationship with age (r = 0.40, p<0.001). Similar relationships were observed in each gender. These data demonstrate the relationship of age with periodontal status, and periodontal status with oral health behaviour. A two‐dimensional matrix of HU‐DBI score by CPITN may provide a simple and effective means of identifying low and high risk individuals.